DISMANTLING THE NOTION OF DIGITAL FREEDOM IN THE CONTEMPORARY ERA: ANALYSING THE ISLAMIC DISCOURSE ON ETHICS, RESPONSIBILITY, AND ITSDYNAMIC INFLUENCE ON TECHNOLOGICAL ADVANCEMENTS - Loso Judijanto; Ismail Nasar; Muhammadong; Khaerunnisa; Mohammad Ahmad Bani Amer (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In the rapidly evolving landscape of the contemporary era, digital freedom has become a focal point, influencing how societies interact with and adapt to technological advancements. This paper undertakes a comprehensive exploration, focusing on the Islamic discourse on ethics and responsibility as a guiding framework in assessing digital freedom. Through a systematic literature review, this study critically examines prevailing notions of digital freedom, analyzes Islamic ethical perspectives, and investigates the dynamic influence of these principles on technological advancements. The discussion encompasses case studies from Islamic countries, global perspectives at the intersection of Islamic ethics and technology, and the implications of this discourse for dismantling conventional ideas surrounding digital freedom. The critique and challenges section provides insights into potential limitations, areas for improvement, and challenges in implementing Islamic ethical principles in the digital age. The implications for future research emphasize the need to explore the adaptability and relevance of Islamic ethical frameworks in the face of emerging technological challenges.